Transformasi Layanan Kebidanan ; Pemberdayaan Ibu Hamil Melalui Hypnopregnancy Sebagai Holistic Care - puspita sari, lutfiana; Astuti, Kh Endah Widhi; Sulastri, Eni (Universitas Nusantara PGRI Kediri, 2025)
Anxiety and depression during pregnancy are common issues with a relatively high prevalence, ranging from 12.5% to 42%. In fact, these disorders were projected to become the second leading cause of disease burden by the year 2020. The Aim to empower pregnant women through hypnopregnancy so they can achieve health in body, mind, and soul by combining physical and psychological therapies. Deep relaxation, concentration/focus, and hypnosis are beneficial for resting the conscious mind and embedding positive “understanding” into the subconscious mind. As a result, daily actions become more influenced by the subconscious, helping individuals become calmer, more centered, and less stressed. The study involved training pregnant women in hypnopregnancy techniques to reduce anxiety and improve both mental and physical well-being. Anxiety levels were measured before and after the hypnopregnancy intervention using the State-Trait Anxiety Inventory (STAI). This instrument includes 20 items assessing anxiety indicators in pregnant women, with a maximum score of 80. STAI scores below 40 indicate low anxiety, while scores above 40 indicate high anxiety. After conducting hypnopregnancy training and prenatal yoga sessions, anxiety levels among the pregnant women decreased. The average anxiety score before the intervention was 34.7, and after the hypno-yoga sessions, it dropped to 24.8. Hypnopregnancy is proven to be effective in reducing anxiety in pregnant women as a form of holistic care during pregnancy. It is important to educate pregnant women on hypnopregnancy practices to help them achieve health in mind, body, and soul. Additionally, hypnopregnancy can be easily applied as a daily exercise routine to support successful childbirth.